Therapeutic effects of inhibition of sphingosine-1-phosphate signaling in hif-2α inhibitor-resistant clear cell renal cell carcinoma - Höfflin, Rouven; Harlander, Sabine; Abhari, Behnaz; Peighambari, Asin; Adlesic, Mojca; Seidel, Philipp; Zodel, Kyra; Haug, Stefan; Uluvar, Burulc̨a; Li, Yong; Lahrmann, Bernd; Grabe, Niels; et al. (Cancers, 2021)
Specific inhibitors of HIF-2α have recently been approved for the treatment of ccRCC in VHL disease patients and have shown encouraging results in clinical trials for metastatic sporadic ccRCC. However, not all patients respond to therapy and pre-clinical and clinical studies indicate that intrinsic as well as acquired resistance mechanisms to HIF-2α inhibitors are likely to represent upcoming clinical challenges. It would be desirable to have additional therapeutic options for the treatment of HIF-2α inhibitor resistant ccRCCs. Here we investigated the effects on tumor growth and on the tumor microenvironment of three different direct and indirect HIF-α inhibitors, namely the HIF-2α-specific inhibitor PT2399, the dual HIF-1α/HIF-2α inhibitor Acriflavine, and the S1P signaling pathway inhibitor FTY720, in the autochthonous Vhl/Trp53/Rb1 mutant ccRCC mouse model and validated these findings in human ccRCC cell culture models. We show that FTY720 and Acriflavine exhibit therapeutic activity in several different settings of HIF-2α inhibitor resistance. We also identify that HIF-2α inhibition strongly suppresses T cell activation in ccRCC. These findings suggest prioritization of sphingosine pathway inhibitors for clinical testing in ccRCC patients and also suggest that HIF-2α inhibitors may inhibit anti-tumor immunity and might therefore be contraindicated for combination therapies with immune checkpoint inhibitors.
Published: 25 September 2021
Gesehen am 27.09.2022